Intraoral Rhabdomyosarcoma in a Young Boy - Aravinda Konidena; Manasi Kode (Wolters Kluwer Medknow Publications, 2010)
Rhabdomyosarcoma constitutes about 10 to 15% of the malignant neoplasms affecting children. Common sites of involvement include the head and neck, extremities and retropentoneum. Intraoral rhabdomyosarcomas are rare and can affect tongue, palate, oral mucosa or gingiva. A case of rhabdomyosarcoma is being reported along with a review of literature.